DEVELOPING PUZZWORLD GAME FOR WRITING SKILL - Yuyun Bahtiar; Nina Zulva Syafaatin; Akhmad Kanzul Fikri (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2021)
The use of ICT in education is a must and can be said to be a necessity in the digital era. This is because it is an effort to create quality learning. PuzzWorld Game (Puzzle World Game) is a technology-based learning media developed as a game that contains various learning materials that have been adapted to the needs of students. However, its existence is still rarely used in the world of education. The existence of ICT in the form of Puzzle Games in English lessons can support learning success because not all students easily understand every subject matter presented. PuzzWorld Game is a solution to student problems because it can facilitate student learning activities. This study examines the use of Puzzle Game media in optimizing English learning in junior high schools, especially in writing skills. A study on the use of the Puzzle Game was conducted in 2021 at Madrasah Tsanawiyah Nurul Qur'an Ploso Jombang with a total of 26 students. This type of research is development research. To analyze the results of the study used descriptive qualitative analysis. Data were obtained through questionnaires and learning outcomes tests. Researchers tested the effect of Puzzle Game Media. The results get 95 was in “very good” category. Through Puzzle Games, students can evaluate learning outcomes well and make it easier to understand the material being studied. The results of this study are very relevant in learning, especially in improving student learning outcomes towards learning English at Junior High School level.